Performance of hybrid maize at different nitrogen levels in spring season at Badhaiyatal area of Bardiya District, Lumbini Province, Nepal - Adhikari, Madhusudhan; Sah, Shrawan Kumar; Ghimire, Binod; Neupane, Prajina (Nepal Agriculture Research Journal, 2023)
Blanket recommendation of nitrogen (N) for maize would not be applicable as the new high yielding hybridshave been grown in Nepal. A field experiment was carried out during spring season at Badhaiyatal, Bardiya to determine optimum N level for hybrid maize. The treatments consisted of three commercial maize hybrids namely Rampur hybrid-10, Rajkumar and Pioneer-3522 and four N levels i.e., 150 kg ha-1, 175 kg ha-1, 200 kg ha-1 and 225 kg ha-1. The experiment was carried out in split-plot design with maize hybrids as main plot factor and N levels as sub plot factor in three replications. Results revealed that all yield attributes were significantly (0.05) influenced by variety and nitrogen levels except number of ears harvested per hectare. The grain yield with N level @ 225 kg ha-1 (8.69 t ha-1) was found higher than remaining N levels. The higher yield with 225 kg N ha-1 was because of significantly (0.05) higher leaf area index (4.67 at 75 Days After Sowing, plant height (248.50 cm at 75 DAS), number of kernels per ear (467), ear length (18.59 cm), ear circumference (15.16 cm) and shelling percentage (70.68%). All three maize hybrids: Pioneer 3522 (8.46 tha-1), Rajkumar (8.05 t ha-1) and Rampur hybrid-10 (7.63 t ha-1) were found similar in grain yield. The yield attributes viz., ear length, and ear circumference number of kernels per ear showed positive correlation with grain yield. Therefore, application of N@ of 225 kg ha-1 for the maize hybrids during spring season is suggested in Bardiya.